Cruise the Baltic Sea! -Collaborating and competing within the Baltic Sea Region - Udo,Regina; Lindgren,Martina; Fogelberg,Malin (2007)
Statement of purpose: The purpose of this report is to enhance the understanding and knowledge of the collaborative destination marketing process. Questions of issues: How do Helsingborg and Stockholm collaborate and compete within the Cruise Baltic Project? What preconditions, motivations and outcomes related to the Cruise Baltic Project exist in Helsingborg and Stockholm? How do they differ? Methodology: The Cruise Baltic Project has been examined through the use of theoretical approaches and conceptions on collaboration, competition and on the collaborative destination marketing process. The research is based on two qualitative interviews at the two destinations Helsingborg and Stockholm and on an examination of printed material on the project. Key words: Collaboration, competition and coopetition. Collaborative destination marketing, Preconditions, motivations and outcomes. Cruising in the Baltic Sea. ______________________________________________________________________ The growth in cruise tourism and the fragmented nature of the cruise industry has lead to a need for collaboration between destinations. While travelling, the cruise tourists visit whole regions, such as “the Caribbean”, “the Mediterranean” and “the Baltic Sea”. The Cruise Baltic Project is a development project where destinations within the Baltic Sea collaborate to increase their competitiveness. The collaboration and the competition within the Cruise Baltic Project are examined from the perspectives of two destinations involvement, Helsingborg and Stockholm. The study found that the destinations together reach a collaborative advantage through increased recognition and improved common standards. The competition between the destinations is intense and has lead to a development of differentiation strategies and unique selling proposition by both Stockholm and Helsingborg. Because the destinations collaborate and compete simultaneously a coopetitive relationship was established. The preconditions for Helsingborg and Stockholm were of a similar nature due to the fact that both destinations were located in Sweden. An important precondition that differed between the two destinations was their geographical location. The study found that the motivations for collaboration were similar between the two destinations, with the common motivation of increasing their competitiveness. Finally, the outcomes of the project were also of a similar nature. A higher recognition, stronger competitiveness and a significant increase of visitors were identified.
Keywords: collaboration; competition and coopetition. collaborative destination marketing; preconditions; motivations and outcomes. cruising in the baltic sea.; Tourism; Turism